Qur’an journaling and self-acceptance among young adults following romantic relationship dissolution - Hasna Hafizhah Salma; Dillo Augustdi Putra; Novi Cahyati; Atri Laranova; Najwa Sabina Putri Dafilia; Sri Rudatin (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2026)
The dissolution of a romantic relationship is a significant emotional experience for young adults and may affect self-acceptance, particularly in collectivistic cultural contexts such as Indonesia, where self-acceptance is often associated with social acceptance. Expressive writing is known to support the process of self-acceptance; however, its integration with Islamic spiritual values remains limited and requires scientific evidence. This study aimed to examine the effect of Quran Journaling on improving self-acceptance among Muslim young adults aged 18,40 years following the dissolution of a romantic relationship. This study employed a quantitative quasi-experimental approach using a one-group pretest,posttest design. The study was conducted online through Zoom and WhatsApp groups. The Quran Journaling intervention was carried out over a one-month period and consisted of four 60-minute sessions. The instrument used in this study was the Self-Acceptance Scale (α = .93). The results showed an increase in self-acceptance scores before and after the intervention (t = 3.459, p < .01), with a Cohen's d effect size of 0.410, based on 30 participants (29 women and 1 man). However, this study was limited by the absence of a control group. Therefore, future researchers may use a control-group design to ensure that the findings are not influenced by maturation effects. The findings of this study may be beneficial for Muslim counselors and psychologists who wish to incorporate Quran Journaling into counseling or therapy sessions, with opportunities for further development of the intervention.